Faktor-Faktor yang Berhubungan dengan Kejadian Anemia pada Remaja Putri di SMA Negeri 14 Bandar Lampung dan SMA IT Baitul Jannah Bandar Lampung - Ladin Juliawan; Anita Bustami; Aryanti Wardiyah (Malahayati Nursing Journal, 2024)
ABSTRACT Lampung Province is the province that has the highest prevalence of anemia on the island of Sumatra with a percentage of 63%. Based on this data, it shows that 24% of anemia sufferers in Lampung Province occur in teenage girls. Based on the results of a pre-survey of 60 students, hemoglobin levels were checked. The results showed The total sample was 213 respondents using Purposive Sampling technique. And analyzed using the Chi Square test.  The results of the chi-square analysis of the relationship between knowledge and the incidence of anemia with a p-value of 0.000 and 0.003. The relationship between diet and the incidence of anemia with a p-value of 0.015 and 0.020. The relationship between menstrual patterns and the incidence of anemia with a p-value of 0.001 and 0.017. The relationship between economic status and the incidence of anemia with a p-value of 0.025. The relationship between consumption of Fe tablets and the incidence of anemia with a p-value of 0.039 and 0.020. Then the relationship between place of residence and the incidence of anemia with a p-value of 0.768. This shows that there is a relationship between knowledge, diet, menstrual patterns, economic status, and table Fe consumption and the incidence of anemia. Then there is no relationship between place of residence and the incidence of anemia. Young women are advised to maintain their diet and consume Fe tablets regularly to prevent anemia. Keywords : Anemia, Adolescent Girls, Anemia Incidence Factors ABSTRAK  Provinsi Lampung adalah Provinsi yang memiliki prevalensi kejadian anemia tertinggi di pulau sumatra dengan persentase 63%. Berdasarkan data tersebut menunjukan bahwa 24% penderita anemia di Provinsi Lampung terjadi pada usia remaja. Berdasarkan hasil pre survey terhadap 60 siswa dengan dilakukan pengecekan kadar hemoglobin. Didapatkan hasil bahwa diketahui faktor-faktor yang berhubungan dengan kejadian anemia pada remaja putri. Jumlah sampel 213 responden dengan teknik Purposive Sampling. Dan dianalisis menggunakan uji Chi Square. Hasil analisis chi-square hubungan antara pengetahuan dengan kejadian anemia dengan nilai p-value 0,001 dan 0,003. Hubungan antara pola makan dengan kejadian anemia dengan nilai p-value 0,015 dan 0,020. Hubungan antara pola menstruasi dengan kejadian anemia dengan nilai p-value 0,000 dan 0,017. Hubungan antara status ekonomi dengan kejadian anemia dengan nilai p-value 0,025. Hubungan antara kosumsi tablet Fe dengan kejadian anemia dengan nilai p-value 0,039 dan 0,020. Kemudian hubungan antara tempat tinggal dengan kejadian anemia dengan niali p-value 0,768. Hal ini menunjukan bahwa ada hubungan antara pengetahuan, pola makan, pola menstruasi, status ekonomi, dan kosumsi table Fe dengan kejadian anemia. Kemudian tidak ada hubungan antara tempat tinggal dengan kejadian anemia. Remaja putri disarankan untuk menjaga pola makan dan mengkosumsi tablet Fe secara teratur untuk mencegah terjadinya anemia. Kata Kunci : Anemia, Remaja Putri, Faktor Kejadian Anemia